2020
DOI: 10.1002/ejic.202000120
|View full text |Cite
|
Sign up to set email alerts
|

Homoleptic Mononuclear Tris‐Chelate Complexes of FeII, CoII, NiII, and ZnII Based on a Redox‐Active Imidazolyl‐2‐thione Ligand: Structural and Electrochemical Correlation

Abstract: Five mononuclear tris‐chelate complexes of FeII, CoII, NiII and ZnII, containing the bidentate ligand 3‐methyl‐1‐(2‐pyridyl)imidazolyl‐2‐thione (L), have been synthesised and characterised, namely [MII(L)3](BF4)2, where M = Fe (1), Co (2), Ni (3) and Zn (4), and [FeII(L)3](PF6)2 {1‐(PF6)2}. The complexes have been characterised by standard methods and single‐crystal X‐ray diffraction, showing that all the complexes are isostructural and isomorphs, crystallising in the P1 space group, except for 1‐(PF6)2, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 74 publications
2
6
0
Order By: Relevance
“…At room temperature the complexes stabilized in the HS‐state show a μ eff value ranging from 4.9 to 5.5 μ B , although for the majority of complexes the value is higher than the expected μ S.O. =4.9 μ B , it is still in good agreement with the high spin state and suggests a considerable orbital contribution to g , [22,27,41] in addition the values are in agreement with the literature [20,42–44] . The room temperature μ eff value for complex 1 a containing the PySBn ligand (Figure 7) indicates that it is stabilized in the HS‐state, the μ eff value is maintained relatively constant down to 25 K, below this temperature zero field splitting (ZFS) is evident.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…At room temperature the complexes stabilized in the HS‐state show a μ eff value ranging from 4.9 to 5.5 μ B , although for the majority of complexes the value is higher than the expected μ S.O. =4.9 μ B , it is still in good agreement with the high spin state and suggests a considerable orbital contribution to g , [22,27,41] in addition the values are in agreement with the literature [20,42–44] . The room temperature μ eff value for complex 1 a containing the PySBn ligand (Figure 7) indicates that it is stabilized in the HS‐state, the μ eff value is maintained relatively constant down to 25 K, below this temperature zero field splitting (ZFS) is evident.…”
Section: Resultssupporting
confidence: 74%
“…All the S‐based ligands contain the same thioether functional group, in combination with amine, pyridine, triazole or pyrazole nitrogen donors, and some of them contain NCE (E=S, Se or BH 3 ) co‐ligands. An advantage of synthesizing S‐containing iron(II) complexes is the protection toward oxidation of the metal centre, as it has been shown that some S‐based ligands are redox non‐innocent, [24–27] preventing the metal centre to oxidize to iron(III), thus ensuring the preservation of the SCO‐properties.…”
Section: Introductionmentioning
confidence: 99%
“…At room temperature the m eff value ranges from 5.00 to 5.41 m B , although for the majority of complexes the value is higher than the expected m S.O. = 4.9 m B , it is still in good agreement with the high spin state and suggests orbital contribution to g, 22,42,43 in addition the values are in agreement with the literature. 6,9,44,45 The family of complexes containing the ImPyS ligand (1a-c, Fig.…”
Section: Paper Njcsupporting
confidence: 86%
“…To the best of our knowledge, there is no examples of first-row transition metal complexes containing more than one bidentate imidazolylthione ligand, except for a recent example of our group in which tris-chelate metal complexes of Fe II , Co II , Ni II and Zn II based on ImPyS ligand have been synthesised and characterised showing that this type of ligands are redox active and that the complex redox potential correlates to the M-N bond length, which in turn relates to the ionic radius of the metal ion, thus permitting to predict the complex redox potential. 22 On the other hand the magnetic properties of first row transition metal complexes based on imidazolylthione ligands have been scarcely investigated, 22,[25][26][27][28][29] whereas for 1,2,3-triazolylthione-based complexes there are no examples available, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of the iron complex of imidazole-2thione chelator IT1 (Figures 3, S4, Table S2) also presents FeÀ S and FeÀ N distances consistent with a ferric center as well as an overall cationic charge balanced by a tetrafluoroborate ion. Whereas several imidazole-2-thione ligands were found to stabilize ferrous ions, [31,32] the incorporation of this moiety in a tridentate mercaptobenzaldehyde hydrazone leads to a stable ferric complex. The two ligands coordinate in meridional fashion but again lack the planarity of a fully delocalized π system.…”
mentioning
confidence: 99%